Associations of Internet Developers - S. S. Shirin (Vestnik MGIMO-Universiteta)
The results of research of participation of international networked associations of internet developers in world political process are presented in the article. The main cases are associations that develop technical standards for the internet or promote such standards (IETF and WaSP), associations that develop countermeasures against the political control of internet communications (Netsukuku, TOR and FreeNet), and an association that develop one of the most remarkable political online projects WikiLeaks.